Employee management and customer service in the retail industry - Heil, Gary (Wiley, 2006)
Employee Management and Customer Service in the Retail Industry, by Gary Heil and Chris Thomas, attempts to combine the psychology of dealing with employees and customers with the practical realities of managing a retail business. Organized into ten chapters, this book loosely follows a retail manager's natural progression from interviewing prospective employees, to hiring the right ones, paying them fairly, and keeping them happy on the job.